2022
DOI: 10.3390/ijms23168976
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Disease during Pregnancy Causes a Systematic Increase in Maternal and Fetal Proinflammatory Markers

Abstract: Chronic venous disease (CVD) is a common vascular disorder characterized by increased venous hypertension and insufficient venous return from the lower limbs. Pregnancy is a high-risk situation for developing CVD. Approximately a third of the women will develop this condition during pregnancy, and similarly to arterial hypertensive disorders, previous evidence has described a plethora of alterations in placental structure and function in women with pregnancy-induced CVD. It is widely known that arterial-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 116 publications
2
19
0
Order By: Relevance
“…Chronic venous disease (CVD) is a vascular disorder characterized by increased venous hypertension and insufficient venous return from the lower limbs [76]. The haemodynamic changes that occur during pregnancy, such as vasodilation, compression of iliac veins and venous stasis, favour its development [77][78][79][80].…”
Section: Chronic Venous Disease During Pregnancy: Placental and Umbil...mentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic venous disease (CVD) is a vascular disorder characterized by increased venous hypertension and insufficient venous return from the lower limbs [76]. The haemodynamic changes that occur during pregnancy, such as vasodilation, compression of iliac veins and venous stasis, favour its development [77][78][79][80].…”
Section: Chronic Venous Disease During Pregnancy: Placental and Umbil...mentioning
confidence: 99%
“…The foetus and neonate are also participants in this proinflammatory state [95]. Some studies have shown that gestational CVD favours this proinflammatory state, as indicated by increases in the levels of proinflammatory cytokines (IL-6, IL-12, TNF-α, IL-10, IL-13, IL-2, IL-7, IFN-γ, IL-4, IL-5, IL-21, IL-23, GM-CSF, chemokines (fractalkine), MIP-3α and MIP-1β) in pregnant women with CVD and in the umbilical cord blood of their newborns [76]. At the foetal and neonatal levels, this proinflammatory profile has been related to multiple pathologies, such as preeclampsia, preterm delivery, and the development of bronchial hyperresponsiveness or overweight during the first years of life and therefore forms part of the so-called "foetal programming" [46,47].…”
Section: Chronic Venous Disease During Pregnancy: Placental and Umbil...mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, pregnancy-associated CVD involves changes at angiogenesis, lymphangiogenesis, with several changes in the extracellular matrix compared with healthy controls (HC) with no history of CVD [ 17 , 18 ]. All in all, these factors could have a negative impact not only on the mother’s life—during and after childbirth—but also on the fetuses’ development [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this condition remains underestimated, early evidence of CVD being frequently overlooked by general practitioners [ 1 ]. Clinical manifestations of CVD can range from mild to severe, such as telangiectasia, varicose veins (most notably), lipodermatosclerosis or venous ulceration, and pain is one of the most common symptoms [ 2 , 3 ]. It is well-known that CVD negatively impacts patient’s quality of life (QoL), both at the physical and the psychological levels [ 4 ].…”
Section: Introductionmentioning
confidence: 99%